"Islam’s White Conquests on the Barbary Coast: Geopolitics, Faith and Sexuality in English Captivity Narratives from Early Modern Maghreb (1678-1769)" - Kettioui Abdelmajid (Université Sidi Mohamed Ben Abdellah, Faculté des Lettres et des Sciences Humaines - Dhar El Mahraz - , Fès, 2018)
This dissertation addresses the intersection of geopolitics, faith and sexuality in the English Barbary captivity narrative from early modern North Africa. It is my contention that historical and literary white captives on the coasts of North Africa constitute in English captivity discourse Islam’s white conquests. In this sense, English captives like Thomas Phelps, Joseph Pitts, Robert Boyle, Mrs. Villars, Thomas Pellow, and Elizabeth Marsh enact the irreconcilable figure of the imperial subaltern. Even when erstwhile captives made it home scathless, it is their contact with Islam that attended and haunted their homecomings and recitals. A site of ordeal but also preferment, the North African coast figures forth as a geopolitical outside to England’s and the Continent’s sweeping settlement colonialism and imperial conquests Atlantic-wise. This dissertation derives its relevance and urgency from the fact that the hostage stories of Anglo-American POWs in Afghanistan and Iraq post-9/11 “war on terror” borrow culturalist clichés on Islam’s sexual prurience and missionary violence from the Barbary captivity discourse. Privileging a Cultural Studies perspective, this dissertation centers on four representative accounts to re-create the story of English captivity in its contemporary context. The captivity narratives of Joseph Pitts (1704), William R. Chetwood (1726), Thomas Pellow (1739) and Elizabeth Marsh (1769) are set against other English and Continental contemporary captivity accounts, journals, royal missives and redemption embassies. These include the writings of Thomas Phelps (1685), Simon Ockley (1713), Daniel Defoe (1720), John Windus (1721), Miss de Bourk (1735), Maria ter Meetelen (1748) and James Sutherland (1768). This dissertation is in three parts. The first is theoretical and sets forth past-colonialism as a theoretical framework for understanding Anglo-Maghrebi maritime encounters in early modernity. Ex-apostates in the Maghreb are theorized through the figure of the reverting renegade as a hybrid subject. The second gives a geopolitical, historical and literary account of captivity in the Maghreb. In the third part, the captivity narratives of Pitts, Pellow, Chetwood, and Marsh are set within their larger historical contexts and, as such, read against other contemporary English accounts of captivity.
Keywords: Cultural studies; Islam; White conquests; Barbary captivity narratives; Joseph Pitts; William R. Chetwood; Thomas Pellow; Elizabeth Marsh; English; North Africa; Geopolitics; Faith; Sexuality; Early modern; Acculturation; Orientalism